Apolipoprotein E gene polymorphism influenced glycemic status among Malaysians - Rahman, K. M. Hafizur; Hossain, Md Sanower; Haque, Nazmul; Abdul Razak, Tariq; Ahmad, Hussain (BioMedPress, 2019)
Aim: In the last decade Apolipoprotein E (APOE) gene polymorphism has been identified as one ofthe risk factors of type 2 diabetes mellitus (T2DM). Though more than 11% population of Malaysiaare suffering from T2DM, there is inadequate data on the correlation between theAPOEgene poly-morphism and pathogenesis of diabetes among Malaysians. Hence, in this study we aimed tofind out the association between the frequencies ofAPOEallele and fasting blood glucose (FBG)concentration among subjects with T2DM.Methods: A total of 102 subjects were recruited intotwo distinct groups, 51 in diabetes (cases) and 51 in non-diabetes (control) group. Their fastingblood sample was tested for FBG, whileAPOEgenotyping was carried out using restriction fragmentlength polymorphism technique. Predictive Analytics Software (PASW) statistics, version 18.0, wasused for statistical analyses.Results: There was no association betweenAPOEalleles and T2DM;odd ratios for the e2, e3 and e4 alleles were 1.51 (95%CI: 0.615-3.706), 0.77 (95%CI: 0.431-1.375) and1.12 (95%CI: 0.584-2.131) respectively. The highest mean FBG was found in subjects with e2 alleles,followed by e4 and e3 alleles in both cases and control groups. Both e2 and e4 alleles were sig-nificantly linked to higher mean FBG (p=0.03 and 0.04 for the respectively) compared to e3 allelein diabetes group.Conclusions: Although theAPOEgene was not found to be associated withT2DM, it may influence glycemic status among subjects.